Perception of higher education students regarding the flipped classroom methodology (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
The study aimed to evaluate the perspective of university students regarding the flipped classroom methodology as an innovative pedagogical strategy for improving knowledge acquisition processes and encouraging teachers to update their teaching models. The methodology was applied during the development of Epistemology course content to 117 second-semester students from the Faculty of Chemical Sciences at the Central University of Ecuador, during the March–August 2019 academic period, using a survey as the instrument. Most students expressed acceptance of the new method, while a small percentage preferred the traditional teaching model. However, students showed a neutral attitude when deciding between the two teaching-learning approaches.